Identification of a Novel Brevibacillus laterosporus Strain With Insecticidal Activity Against Aedes albopictus Larvae - Barbieri, Giulia; Ferrari, Carolina; Mamberti, Stefania; Gabrieli, Paolo; Castelli, Michele; Sassera, Davide; Ursino, Emanuela; Scoffone, Viola Camilla; Radaelli, Giacomo; Clementi, Emanuela; Sacchi, Luciano; Ferrari, Eugenio; et al. (Frontiers in Microbiology, 2021)
Bacterial species able to produce proteins that are toxic against insects have been discovered at the beginning of the last century. However, up to date only two of them have been used as pesticides in mosquito control strategies targeting larval breeding sites: Bacillus thuringensis var. israelensis and Lysinibacillus sphaericus. Aiming to expand the arsenal of biopesticides, bacterial cultures from forty-four soil samples were assayed for their ability to kill larvae of Aedes albopictus. A method to select, grow and test the larvicidal capability of spore-forming bacteria from each soil sample was developed. This allowed identifying thirteen soil samples containing strains capable of killing Ae. albopictus larvae. Among the active isolates, one strain with high toxicity was identified as Brevibacillus laterosporus by 16S rRNA gene sequencing and by morphological characterization using transmission electron microscopy. The new isolate showed a larvicidal activity significantly higher than the B. laterosporus LMG 15441 reference strain. Its genome was phylogenomically characterized and compared to the available Brevibacillus genomes. Thus, the new isolate can be considered as a candidate adjuvant to biopesticides formulations that would help preventing the insurgence of resistance.